UPAYA PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN MENGGUNAKAN METODE IQRA’ DI DTA ASY-SYIFA PERMATA - Neng Nila Nursafaat; Haerudin; Rahma Dilla Zainuri (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Initiatives to Improve the Ability to Read the Qur'an by Using the Iqra' Method at DTA Asy-Syifa Permata. This study aims to assess initiatives aimed at improving fourth grade students' Qur'an reading ability at DTA Asy-Syifa Permata through the Iqra' technique. This research uses qualitative methodology through case studies, focusing on teachers and students as the main subjects. The data obtained consisted of interviews, direct observation at school, and documentation, which were then evaluated thematically. The study concluded that the Iqra technique improves students' ability to read the Qur'an through various stages. Nonetheless, internal and external obstacles, including students' lack of aptitude and motivation from educators and parents, must be overcome through initiatives such as implementing regular Qur'ānic reading practice using the Iqra' method, using creative and innovative educational media, giving praise to students, and gaining a deeper understanding of students' abilities and personalities.